Caracterização microestrutural de ligas de alumínio AA5052- H32 e AA6082-T6 - Frederico Dias Silveira (2024)
The use of aluminum and its alloys in various industrial sectors, such as the agricultural sector, is not without problems, many of which are linked to corrosive processes. The microstructural characterization of aluminum alloys is fundamental as the microstructure influences the mechanical and chemical properties of the alloys. The present work aimed to microstructurally characterize the aluminum alloys AA5052-H32 and AA6082-T6, commonly used in the agricultural sector. In summary, the results of the microstructural characterization tests demonstrated that, in general, the precipitates from the AA5052-H32 alloy presented larger and much more heterogeneous surface areas than those from the AA6082-T6 alloy. It was noticeable that the AA5052-H32 alloy presented grooves/cracks and the AA6082-T6 alloy presented variations in thickness, characteristics inherent to the type of treatment used and the influence of temperature on the process. Transmission electron microscopy (TEM) tests and chemical mapping were used to observe the most common intermetallic precipitate phases mentioned in the literature. The AA5052-H32 alloy presented an average precipitate area of 30.53 μm2 ± 25.52 μm2 and the AA6082-T6 alloy presented an average inclusion area of 6.37 μm2 ± 2.42 μm2 calculated from electron microscopy micrographs scan. used. The alloy AA5052-H32 presented an average area of precipitates of 0.0232 μm2 ± 0.0184 μm2 and the alloy AA6082-T6 presented an average area of inclusions of 0.0064 μm2 ± 0.0046 μm2 calculated from electron microscopy micrographs transmission. The rod-shaped Mg2Si and Mg2Al3 phases were identified in the AA5052-H32 alloy using transmission electron microscopy. In the AA6082-T6 alloy, polygonal Al-Fe-Mn-Si inclusions were identified, which became even more evident in the chemical mapping of the alloy surface. The Mg2Si phase was observed in network and needle morphology. In general, it was inferred that the scale used in the mapping was not adequate to observe the precipitates that contained Mg in their composition, since Mg was quite dispersed in the matrix for both alloys.